Sexual encounters : Pacific texts, modern sexualities - Wallace, Lee, 1962- (Cornell University Press, 2003)
The subject of Sexual encounters is sexual fantasy, particularly male homoerotic fantasy found in the literature and art of South Sea exploration, colonization, and settlement. Wallace engages in subversive readings of eighteenth and nineteenth-century Pacific voyage journals (Cook in Hawaii and a Russian expedition to the Marquesas), reassesses Gauguin's treatment of female figures, and discusses homosexuality and Samoan male-to-female transgenderism. These phenomena, Wallace asserts, demonstrate the continuity and dissonance between Western and Pacific sexual categories.